Changing trends and characteristics of one punch deaths in Australia (2012–2018). (April 2023) - Schumann, Jennifer L.; Sarkar, Reena; Grbic, Marko; Drummer, Olaf H.; Gerostamoulos, Dimitri; Iles, Linda; Bassed, Richard
Abstract: One-punch assaults also known as 'coward punches', are characterised by a single severe blow to the head causing the victim to lose consciousness, resulting in a secondary impact between the head and surrounding environment. Such impacts may result in brain injury leading to fatality or permanent neurological impairment. In a previous publication, there were 90 one punch deaths around Australia between 2000 and 2012, mostly involving young men drinking alcohol at a licensed venue at the weekend. This prompted a surge of public education and awareness campaigns around Australia, in addition to regulatory and legislative changes aimed at curbing social violence. This retrospective descriptive study aimed to examine one punch deaths since 2012 in Australia to determine if there has been a decrease in deaths, and whether the demographics and circumstances of these deaths have changed. A search of the National Coronial Information System was undertaken for all closed coronial cases between 1 January 2012 and 31 December 2018. Additional information was collected from medicolegal reports including toxicology, pathology and coronial findings. There were 80 one punch fatalities in Australia, almost exclusively involving males. The median age was 43.5 (range 18–71) years and there was a decreasing trend in the number of deaths annually. Most fatal assaults occurred in the state of New South Wales (28.8%) followed by Queensland (23.8%), and in metropolitan locations (64.6%) rather than regional areas (35.4%). Alcohol was the most commonly detected drug, found in 47 cases of the 71 cases where toxicology results were available (66%), with a median concentration of 0.14 and 0.19 g/100 mL in antemortem and postmortem samples, respectively (range 0.005–0.32 g/100 mL). Five deaths reported methylamphetamine, with THC detected in 21.1% of cases. Assaults more commonly occurred on a footpath or roadside (41.3%), followed by a home or dwelling (32.5%). 8.8% of assaults occurred inside hotels, bars or other licenced venues. Most transpired on a weekday, which differed from the pre-2012 period when these assaults occurred mainly on the weekend. While some trends are positive, there has been a shift in the victim demographic as well as the typical environment for fatal one punch assaults, highlighting the importance of public health surveillance in providing a current evidence base to inform policy and practice. Highlights: There were 80 one punch fatalities in Australia between 2012 and 2018, totalling 169 since 2000. There was a slight decline in the number of deaths annually and those occurring at licensed venues. The median age of victims has increased, along with the proportion of deaths occurring in the home. Illicit drugs detections were rare; alcohol remains the most commonly detected drug in victims. These findings update our evidence base of one punch assaults to inform policy and prevention.